SELERA PASAR TEH RUSIA TERHADAP TEH HITAM ORTHODOX CURAH - ROHAYATI SUPRIHATINI (SOCA: Jurnal Sosial Ekonomi Pertanian, 2004)
A study on tea market preference is required in order to increase market share of Indonesiantea in Russian Federation. Russian Federation market prefers a medium grown tea, whichdominate broken grade (91%). Minimum requirement for all organoleptic attributes(appearance, taste, colour, flavour, and infused leaf) is medium score. Most of tea deffects arenot accepted are only main deffects. Packaging, delivery, and payment method prefer arepaper sack, Free on Board (FOB), and Letter of Credit (L/C), respectively.